Sphingomyelin Synthases in Neuropsychiatric Health and Disease - Mühle, Christiane; Bilbao Canalejas, Roberto; Kornhuber, Johannes (Neurosignals, 2019)
Sphingomyelin synthases (SMS) catalyze the conversion of ceramide and phosphatidylcholine to sphingomyelin and diacylglycerol and are thus crucial for the balance between synthesis and degradation of these structural and bioactive molecules. SMS thereby play an essential role in sphingolipid metabolism, cell signaling, proliferation and differentiation processes. Although tremendous progress has been made toward understanding the involvement of SMS in physiological and pathological processes, literature in the area of neuropsychiatry is still limited. In this review, we summarize the main features of SMS as well as the current methodologies and tools used for their study and provide an overview of SMS in the central nervous system and their implications in neurological as well as psychiatric disorders. This way, we aim at establishing a basis for future mechanistic as well as clinical investigations on SMS in neuropsychiatric health and diseases.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Sphingomyelin synthase; Neurological disease; Psychiatric disease; Brain; Central nervous system